Quantification of imatinib in human serum: validation of a high-performance liquid chromatography-mass spectrometry method for therapeutic drug monitoring and pharmacokinetic assays - Rezende VM; Rivellis A; Novaes MM; Chamone DA; Bendit I (Dove Medical Press, 2013)
Vinicius Marcondes Rezende,1 Ariane Rivellis,1 Mafalda Megumi Yoshinaga Novaes,1 Dalton de Alencar Fisher Chamone,2 Israel Bendit1,21Laboratory of Tumor Biology, 2Department of Hematology, School of Medicine, University of São Paulo, São Paulo, BrazilBackground: Imatinib mesylate has been a breakthrough treatment for chronic myeloid leukemia. It has become the ideal tyrosine kinase inhibitor and the standard treatment for chronic-phase leukemia. Striking results have recently been reported, but intolerance to imatinib and noncompliance with treatment remain to be solved. Molecular monitoring by quantitative real-time polymerase chain reaction is the gold standard for monitoring patients, and imatinib blood levels have also become an important tool for monitoring.Methods: A fast and cheap method was developed and validated using high-performance liquid chromatography-mass spectrometry for quantification of imatinib in human serum and tamsulosin as the internal standard. Remarkable advantages of the method includes use of serum instead of plasma, less time spent on processing and analysis, simpler procedures, and requiring reduced amounts of biological material, solvents, and reagents. Stability of the analyte was also studied. This research also intended to drive the validation scheme in clinical centers. The method was validated according to the requirements of the US Food and Drug Administration and Brazilian National Health Surveillance Agency within the range of 0.500–10.0 µg/mL with a limit of detection of 0.155 µg/mL. Stability data for the analyte are also presented.Conclusion: Given that the validated method has proved to be linear, accurate, precise, and robust, it is suitable for pharmacokinetic assays, such as bioavailability and bioequivalence, and is being successfully applied in routine therapeutic drug monitoring in the hospital service.Keywords: imatinib, high-performance liquid chromatography-mass spectrometry, therapeutic drug monitoring, development, validation